PERANCANGAN WAYFINDING PADA KAWASAN KANTOR PUSAT ADMINISTRASI LANTAI DUA INSTITUT TEKNOLOGI SEPULUH NOPEMBER SURABAYA: Indonesia - Tristya Salsabilla, Safira; Noor Virgiani, Dima; Tri Santoso, Sarah (Universitas Budi Luhur, 2023)
The ITS Surabaya Administration Headquarters (KPA) is a place to serve various types of needs (services and materials), and handle multiple problems, as well as an open space facility for ITS residents to gather for certain events. The number of units and services available at KPA causes many visitors to arrive daily. However, visitors who want to come often have difficulty finding KPA locations and units because wayfinding and signage are still not well integrated, so an EGD design is needed to provide design solutions to the problems encountered with the aim that visitors can be more focused and reduce the level of mental loading. The research method used in this design involves interviews, observation, documentation, and literature study. Changes in the name and location of the units that are carried out every five years after the change of chancellor change the design of KPA buildings and facilities so that it becomes a consideration for innovating signage designs that show a smart eco campus by procuring signage that is flexible and can be disassembled.